Adquisición de competencia para la micropagación de Stanhopea tigrina, Laelia anceps, Epidendrum veroscriptum y Cattleya x Esbetts (Orchidaceae) - Tinoco Juárez, Mario Sinaí; Mata Rosas, Martín (Lankesteriana: International Journal on Orchidology, 2015)
Regeneration protocols were established from the in vitro culture of protocormos of Stanhopea tigrina, Epidendrum veroscriptum, Laelia anceps and Cattleya x esbetts using the Murashige and Skoog culture medium added with different concentrations of N6-benzyladenine (BA) (0, 1, 3, y 5 mg/l) y 2,4 dichlorofenoxiacetic acid (2,4-D). The regeneration and formation of new plantlets was achieved by multiple shoot and also through protocorm like bodies (PLBs). For each species the best concentration of growth regulator, as well as the time of acquisition of competence for the highest shoot formation and/or PLBs were deter- mined. As far as we know there are no reports with reference to the acquisition of competence within the Orchidaceae family that allow the production of many individuals within the shortest time and reducing the financial cost. This could form the base that covers their commercial demand and also contribute to the con- servation and sustainable use of mainly wild species.